Age- and gender-specific adaptability and functionality rates of highly-skilled athletes - Pogodina, S. V.; Aleksanyants, G. D. (Theory and Practice of Physical Culture, 2017)
Series of tests were performed under the study to rate the adaptation processes in the key body systems of highly-skilled 16-46 year-old athletes (male and female) with application of immunological, biochemical, haematological, rheographic, spirographic and anthropometric methods; exhaled gas analysis; and workload tests to profile the age-specific variations of the athletes` functionality, anthropometrical measurements and physicality to explain the natural reduction of the integrated bio-energy rates in the period of 37-46 years of age. The study data and analyses made it possible to find the age-specific changes in the bio-energy resources under specific loads, including: intensive production of lactic acid in the anaerobic-aerobic work modes in the 16-18 year-old and particularly 22-26-year-old athletes; and intensive production of lactic acid in the anaerobic-aerobic work modes in the 37-46 year-old athletes. The study found the following age-specific tensions in the adaptation process: unspecific responses at the relatively high activation level in the male age groups of 17-26 and 40-46 years; fall in the activation level in the male age group of 22-26 years; and the unspecific responses at the relatively high activation level in the female age group of 40-45 years. The study found the age-specific fast adaptation responses of the core body systems in the male group under high-intensity loads, including: growth in the hormonal-metabolic responses in the 17-18 year-old males; general growth of the adaptation responses of the core body systems in the 22-26 year-old males; and weakening of the ventilatory and metabolic responses in the 40-46 year-old males. Furthermore, the study found some chrono-biological regularities in the adaptation processes in the 16-45 year-old females including the high probability of detriment to the ovulatory and menstrual cycles at the age of 37-45 years; weakening of the hormonal responses in the inter-menstrual periods; and specific variations in the autonomic influences in the 37-45 year-old females with the anovulatory cycle and in the 16-26 year-old females with the ovulatory and menstrual cycles versus the hemodynamic and ventilator functions.